2021
DOI: 10.1039/d1cp00102g
|View full text |Cite
|
Sign up to set email alerts
|

Hidden polymorphism of FAPbI3 discovered by Raman spectroscopy

Abstract: Formamidinium lead iodide (FAPbI3) can exhibit polymorphism at ambient conductions. Three different structural configurations and their thermally activated phase transitions are identified by temperature dependent micro-Raman spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…Moreover, in FAI, the molecules are directly connected to each other, and due to the spatial position of the molecule, they can rotate without affecting the bonds. We have previously shown that the structural instability of FAPbI 3 is likely a consequence of the out-of-plane rotation of FA + around its N–N axis . The interaction between the molecule and the inorganic frame is weak ionic by nature, as discussed above.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Moreover, in FAI, the molecules are directly connected to each other, and due to the spatial position of the molecule, they can rotate without affecting the bonds. We have previously shown that the structural instability of FAPbI 3 is likely a consequence of the out-of-plane rotation of FA + around its N–N axis . The interaction between the molecule and the inorganic frame is weak ionic by nature, as discussed above.…”
Section: Discussionmentioning
confidence: 81%
“…High frequency range of the experimental Raman spectra measured for FAPbI 3 (α δ and δ) and FAPbBr 3 at RT.…”
Section: Resultsmentioning
confidence: 99%
“…This result shows an effective band gap modulation due to the alteration of the alkylation groups on btz derivative counter cations in the inorganic lead iodine system . The band gaps of 1a–3 are larger than that of the PbI 3 -type hybrid materials with aliphatic organic counter cations, such as MAPbI 3 (1.53 eV, MA = CH 3 NH 3 + ), FAPbI 3 [1.5 eV, FA = NH 2 (CH) NH 2 + ], and (C 4 H 9 FN) 2 PbI 4 (2.44 eV) . This finding about aromatic and aliphatic moieties to modulate the band gap of hybrid haloplumbates is consistent with our previous study in hybrid iodoargentates .…”
Section: Resultsmentioning
confidence: 91%
“…13 This assignment has been used in numerous studies 24–26 since, even though the cubic Pm 3̄ m symmetry of the α-phase is predicted to be Raman inactive by group theory. Two recent reports by Driscoll et al 27 and Ibaceta-Jana et al 28 dissent from these previous assignments and provide experimental data supporting the assignment of the α-phase as Raman inactive.…”
Section: Introductionmentioning
confidence: 76%